(3QSGdI aj GdJYQjHs - (3GdQHGVjs ((3YHO GdaJGM Hf MSf Hf eMehO Hf CMeO Hf MSf GdehUdi s)
(3ChdgG (B:s
(3hHYO , agPg QSGdI ai GdJYQjH Ydi JQJjH Cfjb hZQjH , LeYJgG Mjf GdJUaM dcJH GddZGJ OaYkG ddEdJHGS , hETGQI HahGFO GdGbJHGS , ebOeI ai GdbGehS s
(3BNQgG (B:s
(3GdgfOGR HGdcSQ hefg GdegfOR debOQ GdbQi , hGHfjI , hEeG UjQhG GdRGi SjfkG , dCfg djS ai cdGege RGi bHdgG OGd , hEfeG cSQhG HfGA aYdGd ai ZjQ GdeVGYa JeJ GdQSGdI , HYfhGf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3eQJHI Ydi MQha GdeYLes
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B- (3GdehUd (B(249) s
Keywords: (3GddZIs